Inhibitory Effect of Delphinidin on Oxidative Stress Induced by H2O2 in HepG2 Cells. (21st November 2020) - Xu, Jingjing; Zhang, Yanwei; Ren, Guofeng; Yang, Rengui; Chen, Jingfang; Xiang, Xiaojing; Qin, Hong; Chen, Jihua
Abstract : Chronic liver diseases (CLDs) are correlated with oxidative stress induced by the accumulation of intracellular reactive oxygen species (ROS). In this study, we employed HepG2, a human liver carcinoma cell line containing many antioxidant enzymes, to explore the function of delphinidin against oxidative stress induced by H2 O2 and to provide scientific data of the molecular mechanism. Cells were pretreated with different concentrations of delphinidin (10  μ mol/L, 20  μ mol/L, and 40  μ mol/L) for 2 h before treatment with 750  μ M H2 O2 for 1 h. The results showed that H2 O2 decreased the survival rate of HepG2 cells and increased the level of ROS, but delphinidin pretreatment could possess the opposite result. At the same time, the expression of Nrf2 was enhanced by the delphinidin pretreatment. This was because delphinidin promoted Nrf2 nuclear translocation and inhibited its degradation, which led to the increase expression of antioxidant protein HO-1 (Nrf2-related phase II enzyme heme oxygenase-1). Besides, we found that delphinidin could significantly alleviate the reduction of Nrf2 protein levels and the accumulation of intracellular ROS levels in Nrf2 knockdown HepG2 cells. In conclusion, our study suggested that delphinidin, as an effective antioxidant, protected HepG2 cells from oxidative stress by regulating the expression of Nrf2/HO-1.